Does Combined Physical and Cognitive Training Improve Dual-Task Balance and Gait Outcomes in Sedentary Older Adults? - Fraser, Sarah A.; Li, Karen Z.-H.; Berryman, Nicolas; Desjardins-Crépeau, Laurence; Lussier, Maxime; Vadaga, Kiran; Lehr, Lora; Minh Vu, Thien Tuong; Bosquet, Laurent; Bherer, Louis (Frontiers in Human Neuroscience, 2017)
Everyday activities like walking and talking can put an older adult at risk for a fall if they have difficulty dividing their attention between motor and cognitive tasks. Training studies have demonstrated that both cognitive and physical training regimens can improve motor and cognitive task performance. Few studies have examined the benefits of combined training (cognitive and physical) and whether or not this type of combined training would transfer to walking or balancing dual-tasks. This study examines the dual-task benefits of combined training in a sample of sedentary older adults. Seventy-two older adults (> 60 years) were randomly assigned to one of four training groups: Aerobic+Cognitive training (CT), Aerobic+Computer lessons (CL), Stretch+CT and Stretch+CL. It was expected that the Aerobic+CT group would demonstrate the largest benefits and that the active placebo control (Stretch+CL) would show the least benefits after training. Walking and standing balance were paired with an auditory n-back with two levels of difficulty (0- and 1-back). Dual-task walking and balance were assessed with: walk speed (m/s), cognitive accuracy (% correct) and several mediolateral sway measures for pre- to post-test improvements. All groups demonstrated improvements in walk speed from pre- (M = 1.33 m/s) to post-test (M = 1.42 m/s, p < .001) and in accuracy from pre- (M = 97.57%) to post-test (M = 98.57%, p = .005).They also increased their walk speed in the more difficult 1-back (M = 1.38 m/s) in comparison to the 0-back (M = 1.36 m/s, p < .001) but reduced their accuracy in the 1-back (M = 96.39%) in comparison to the 0-back (M = 99.92%, p < .001). Three out of the five mediolateral sway variables (Peak, SD, RMS) demonstrated significant reductions in sway from pre to post test (p-values < .05). With the exception of a group difference between Aerobic+CT and Stretch+CT in accuracy, there were no significant group differences after training. Results suggest that there can be dual-task benefits from training but that in this sedentary sample Aerobic+CT training was not more beneficial than other types of combined training.